h.hofstede (h.hofstede@hogeland.nl)

       
1. a. y'' + 8y = 5  met  y(0) = 3  en  y'(0) = 3
L(y'' + 8y) = L(5)
s2L(y) - sy(0) - y'(0) + 8L(y) = L(5)
L(y) (s2 + 8) - 3s - 3 = L(5)
   
    L(y) (s2 + 8) - 3s - 3 = 5/s
L(y) (s3 + 8s) = 3s + 3
L(y) = (3s + 3)/(s + 8s)
       
  b. y''  - 2y' + y  = ex  met  y(0) = -1  en  y' (0) = 1
L(y''  - 2y' + y) = L(ex)
s2L(y) - sy(0) - y'(0) - 2sL(y) + 2y(0)  + L(y) = L(ex)
L(y) (s2 - 2s + 1)  + s - 1 + 2 = L(ex)
L(y) (s - 1)2  + s + 1  = L(ex)
   
    (Dat laatste geldt overigens alleen als s > 1)  
    L(y) (s - 1)2  + s + 1 = 1/(s - 1)
L(y) (s - 1)3 + s2 - 1 = 1
L(y) (s - 1)3 = 1 - s2
L(y) = (1 - s)/(s - 1)
       
  c. y''  + 5y'  + 6y = x  met  y(0) = y' (0) = 2
L(y''  + 5y'  + 6y ) = L(x)
s2L(y) - sy(0) - y'(0) + 5sL(y) - 5y(0) + 6L(y) = L(x)
L(y) (s2 + 5s + 6)  - 2s - 2 - 10 = L(x)
L(y) (s2 + 5s + 6)  - 2s - 12 = L(x)
   
    L(y) (s2 + 5s + 6)  - 2s - 12 = 1/s
L(y) (s4 + 5s3 + 6s2) - 2s3 - 12s2 = 1
L(y) (s4 + 5s3 + 6s2) = 2s3 + 12s2 + 1
L(y) = (2s + 12s + 1)/(s4 + 5s3 + 6s2)
       
2. a.
    L(f ''') = -f ''(0) + s (s2L(f) - sf(0) - f '(0))
L(f ''') = s3L(f) - f '' (0)  - sf '(0) - s2f(0)
 
       
  b. L(f)
L(f ') =  sL(f) - f(0)
L(f '') = s2L(f) - sf(0) - f '(0)
L(f ''') = s3L(f) - f '' (0)  - sf '(0) - s2f(0)

Het "rijtje" hierboven  voortzetten geeft:
L(f n) = snL(f) - f (n - 1)(0) - sf (n - 2)(0) - s2f (n - 3)(0) - .... - snf(0)
       

h.hofstede (h.hofstede@hogeland.nl)